Self-concept of young adolescents based on their birth order - Alcasid, Patricia Sofia O.; Quijano, Ma. Lourdes M.; Catalan, Paula Mae F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The purpose of this research is to determine the characteristics and the self-concept of young adolescents in different areas according to their birth order and how birth order affects one?s self-concept. A survey was conducted to 60 young adolescents from Marikina City and Quezon City high schools using the adapted list of birth order characteristics and the Burnett Self Scale. Among the 60 respondents, 30 young adolescents were randomly chosen for an interview. Through One-Way Analysis of Variance (ANOVA) Test and computation of percentages, data were analyzed. Results show that some characteristics are possessed by other adolescents from different birth orders. Thus, birth order has no effect as well to the self-concept of the young adolescents in different areas.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Self-perception -- Philippines; Birth order -- Philippines